CONTEMPORARY MEDIA AS TOOL OF WAR PROPAGANDA: IMPLICATION FOR THE RIGHTS TO FREEDOM OF OPINION AND EXPRESSION - Bećirović-Alić, Maida; Šaljić, Eldar (The Review of International Affairs, 2026)
Modern technologies and digital channels of communication have a significant impact on public opinion and the dynamics of propaganda, because in modern armed conflicts and international affairs, the media do not have the role of only transmitting information, but become key instruments in shaping narratives that can contribute to the legitimization of military actions, the demonization of the enemy, and the relativization of human rights violations. This paper analyzes the role of the media as a means of war propaganda and examines the consequences that such use has on the realization of the right to free opinion and expression, as one of the fundamental rights guaranteed by international documents. Through a normative analysis of international instruments and case studies, the paper explores the boundaries between free expression and war propaganda, as well as the risks that media manipulation carries for democratic discourse. Special emphasis is placed on the phenomenon of selective empathy, censorship and self-censorship, but also on the challenges that arise from the spread of misinformation on social networks. In addition, the paper examines how contemporary information environments shape war narratives through both geopolitical narrative competition and specific communication techniques such as emotional framing, visual personalization and algorithmically mediated visibility. This paper aims to offer a critical review of contemporary media practices in the conditions of armed conflicts and to point out the need for balancing between the right to information and protection against the instrumentalization of the public through propaganda.